The Role of the Russian Language in the Historic and Cultural Development of the Arctic Region of the Russian Federation (as Exemplified by the Murmansk Region) - Nikolaevna Ivanishcheva, Olga; Vjacheslavovna Koreneva, Anasstasija; Vjacheslavovna Burtseva, Alexandra; Alexandrovna Rychkova, Tatjana (International Journal of Engineering and Technology, 2018)
The article aims to analyze the functioning of the Russian language within the ethnic space of the Murmansk Region. The analysis of the state statistical and archive documents for the Murmansk Region has shown that the Russian language has dominated within the region since at least the 18th century, and this had its obvious economic and communicative advantages, in particular, in education. The Saami, the indigenous small-numbered people of the Murmansk Region, understood and mastered the conversational Russian language since the 18th century. The Russian language dominates within the current polyethnic linguistic environment of the Murmansk Region due to the numerical superiority of the Russians in the region, as well as due to its position as the language of the dominant ethnic group.Â